Econometric modeling of the effect of COVID-19 on ASEAN utility companies’ stock performance and risk profile - David, Frederico Miguel T. (Animo Repository, 2023)
In 2019 the COVID-19 pandemic began, the disease spread rapidly amounting to multiple casualties that ultimately forced the world into exercising strict medical procedures including, but not limited to, workplace closures and school closures. This study examined how the COVID-19 pandemic affected specific South-East Asian nations' utility sector’s performance. Two models were generated with one model having Stock Returns and the other having Market Index as the dependent variables were tested with whether the COVID Stringency Index, the country of origin, and the time were significant predictors. The model used was a random effects model from Panel Data Analysis. The findings suggest that investors should consider the pandemic's effects while making investment decisions in the region's utilities sector. The research highlights the importance of employing risk management strategies and diversifying portfolios when investing in utility stocks. Additionally, the economic models utilized offer relevant insights into how the COVID-19 pandemic affected the utilities industry. The study also highlighted the significant impact that a government's COVID-19 response may have on the performance of the utilities sector and the region's larger market indexes. The performance of the utility stock in the area was found to be significantly influenced by the COVID-19 stringency index. This emphasizes the criticality of regional governments finding a middle ground between implementing measures to contain the epidemic and maintaining economic stability, while also ensuring the resilience of the utilities sector. In order to grasp an understanding of the utilities industry and broader market indices amidst the COVID-19 outbreak, it may be beneficial to incorporate external factors such as governmental interventions into econometric models. The results of this study also emphasize how crucial it is to comprehend how the utilities industry and larger regional market indices are affected by outside forces like natural catastrophes, political unrest, or economic crises.